1996
DOI: 10.1139/m96-010
|View full text |Cite
|
Sign up to set email alerts
|

Levels and identities of nonrhizobial microorganisms found in commercial legume inoculant made with nonsterile peat carrier

Abstract: Sixty samples of commercial North American legume inoculants manufactured for sale in 1994 using nonsterile peat as carrier were tested for Rhizobium (or Bradyrhizobium) content and non-Rhizobium biological contaminant load. Products of three major producers of such inoculants for sale in Canada were examined. Viable Rhizobium content varied from 5.6 x 10(5) to 8.1 x 10(9) cells/g, while the contaminant load varied from 1.8 x 10(8) to 5.5 x 10(10) cfu/g. Most of the inoculants contained more nonrhizobial organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…243 Numerous different carrier materials have been used including biosolids, charcoal-amended soil, clay, lignite, manure, and peat. 11,13,104,113,164,243 Most of the research on the different carrier materials has been for agricultural legume inoculants, with peat being the most commonly used. 164,243,244 Research has indicated that presterilization of the carrier can increase the inoculant's shelf life.…”
Section: Cell Bioaugmentation a Carrier And Encapsulation Technomentioning
confidence: 99%
See 1 more Smart Citation
“…243 Numerous different carrier materials have been used including biosolids, charcoal-amended soil, clay, lignite, manure, and peat. 11,13,104,113,164,243 Most of the research on the different carrier materials has been for agricultural legume inoculants, with peat being the most commonly used. 164,243,244 Research has indicated that presterilization of the carrier can increase the inoculant's shelf life.…”
Section: Cell Bioaugmentation a Carrier And Encapsulation Technomentioning
confidence: 99%
“…11,13,104,113,164,243 Most of the research on the different carrier materials has been for agricultural legume inoculants, with peat being the most commonly used. 164,243,244 Research has indicated that presterilization of the carrier can increase the inoculant's shelf life. 228 The results of Van Dyke and Prosser 242 also demonstrate that preincubation of the inoculant in a sterile carrier can enhance its ultimate survival in environment.…”
Section: Cell Bioaugmentation a Carrier And Encapsulation Technomentioning
confidence: 99%
“…This is surprising considering that some of the contaminants that have been detected in non-sterile peat inoculant products are antagonistic to rhizobia (3). This is surprising considering that some of the contaminants that have been detected in non-sterile peat inoculant products are antagonistic to rhizobia (3).…”
Section: Field Comparison Of Alfalfa Seedmentioning
confidence: 99%
“…Commercial products include both sterile and non-sterile formulation, but in North America, most inoculant products are prepared with non-sterile peat (2,3). Olsen et al (3,4) examined North American inoculants using non-sterile peat and found a high frequency of non-rhizobial contaminants. However, it is unclear whether the relative effectiveness of inoculants manufactured using non-sterile peat is different from those made using sterile peat.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, much of the rhizobial inoculant produced in the world today is of poor quality (Somasegaran 1991;Brockwell and Bottomley 1995). Recent documentation exists of legume inoculant sold, in both developed and developing countries, that contained no detectable rhizobia (Thompson 1991;Olsen et al 1996a).…”
mentioning
confidence: 99%